Subjective feeling of re‐experiencing past events using immersive virtual reality prevents a loss of episodic memory - Bréchet, Lucie (Brain Behav, 2020)
INTRODUCTION: Personally meaningful past episodes, defined as episodic memories (EM), are subjectively re‐experienced from the natural perspective and location of one's own body, as described by bodily self‐consciousness (BSC). Neurobiological mechanisms of memory consolidation suggest how initially irrelevant episodes may be remembered, if related information makes them gain importance later in time, leading for instance, to a retroactive memory strengthening in humans. METHODS: Using an immersive virtual reality system, we were able to directly manipulate the presence or absence of one's body, which seems to prevent a loss of initially irrelevant, self‐unrelated past events. RESULTS AND CONCLUSION: Our findings provide an evidence that personally meaningful memories of our past are not fixed, but may be strengthened by later events, and that body‐related integration is important for the successful recall of episodic memories.